2017
DOI: 10.1002/ajpa.23147
|View full text |Cite
|
Sign up to set email alerts
|

Beyond food: The multiple pathways for inclusion of materials into ancient dental calculus

Abstract: Dental calculus (mineralized dental plaque) was first recognised as a potentially useful archaeological deposit in the 1970s, though interest in human dental calculus as a resource material has increased sharply in the past few years. The majority of recent research has focused on the retrieval of plant microfossils embedded in its matrix and interpretation of these finds as largely the result of deliberate consumption of plant-derived food. However, while most of the material described in published works does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 123 publications
(185 reference statements)
0
114
1
10
Order By: Relevance
“…Items found in dental calculus represent an unknown but tiny, random amount of material that entered the mouth in one of various ways, including ingestion in food, as medication, residues from cultural activities or through breathing [84]. In the case of starchy food, each item eaten will contain billions of starch granules.…”
Section: Dental Calculusmentioning
confidence: 99%
“…Items found in dental calculus represent an unknown but tiny, random amount of material that entered the mouth in one of various ways, including ingestion in food, as medication, residues from cultural activities or through breathing [84]. In the case of starchy food, each item eaten will contain billions of starch granules.…”
Section: Dental Calculusmentioning
confidence: 99%
“…In all cases, these are considered to represent traces of the paleoenvironment, except in the case of Power et al who suggested that the presence of fungal spores represented consumption of identifiable mushrooms . However, food comes from the fruiting body of fungi rather than the spores, which, as small, abundant, inhalable airborne materials, are more likely to be paleoenvironmental indicators . Though fungal spores can be abundant in dental calculus, their close study has yet to be developed, principally due to the very large number of fungal species and limited reference collections.…”
Section: Categories Of Materials Recovered From Dental Calculusmentioning
confidence: 99%
“…Therefore, access to new, direct evidence for ingestion of plant food and evidence for cooking in the Middle Paleolithic were understandably met with optimism. However, items can enter the mouth and become embedded in dental calculus in many ways in addition to food, including as medication, remains of cultural activities and through breathing . Recovered material therefore represents a wide range of dietary, paleoenvironmental and cultural activities that can only be considered on a qualitative (i.e., presence/absence) basis.…”
Section: Introductionmentioning
confidence: 99%
“…Jeden z důležitých výzkumů využívajících paleogenetiky i genetiky současných populací je studie genetické adaptace anatomicky moderního člověka na tepelně upravovanou potravu (Zink, Lieberman 2016, Radini et al 2017, která prokazuje, že mechanicky a tepelně upravovaná potrava je pro člo-věka výhodnější z hlediska efektivity trávení. To například prokazují srovnávací genetickou analýzou enzymatického aparátu trávení.…”
Section: Jak Současná Paleogenetika Přispívá Ke Změně Našeho Chápání unclassified